PENGARUH STRES KERJA TERHADAP KINERJA PEGAWAI BANK DI INDONESIA - Syahfina Agustin; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Work stress is a condition in which there are one or several factors in the workplace that interact with workers so that they interfere with physiological conditions and behavior. Job stress will arise when there is a gap between individual abilities and the demands of the job. Literature review This study aims to determine the effect of work stress on the performance of bank employees in Indonesia. This study uses the literature review method by collecting journals through online databases such as Google and Google Scholar. Inclusion criteria such as the year of the article in the 2018- 2023 period. Journals that do not meet these criteria will be excluded, so that 6 journals will be reviewed. Then the journals are analyzed one by one by looking for similarities and differences in journals and then conclusions are drawn